Cytogenetics and biogeography: considerations about the natural rrigin of hoplias malabaricus (Characiformes, Erythrinidae) on the Iguaçu River - Vicari, Marcelo Ricardo; Pazza, Rubens; Artoni, Roberto Ferreira; Margarido, Vladimir Pavan; Bertollo, Luiz Antonio Carlos (My University, 2006)
Hoplias malabaricus (trahyra) is a widespread fish species over the Neotropical region with diversified inter-populational karyotypes (cytotypes), which may correspond to a species complex. Despite the wide distribution in the South American basins, some authors have questioned its natural origin in the Iguaçu river, an important Brazilian river basin which is characterized by several endemic fish species. We have analyzed the karyotype of H. malabaricus from different collection sites of this river, by conventional and banding methods. Our results, in addition to our previous data concerning geographic distribution of the cytotypes, contribute to better understand the origin of H. malabaricus on the Iguaçu river, reinforcing the proposition that it is a natural fish species in this river basin.
Keywords: Chromosome evolution; Karyotypes distribution; Endemism